Comparison as a Sign of Artistic Idiolect (Basing on Material of Stus’ Poetic Language) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article studies the comparisons as a specific feature of Stus’ artistic language in collection of poems “Palimpsests”. It has been defined that the author's individual linguistic worldview represents key life concepts through comparisons and opens the subliminal words of the artist, who sees everyday reality in unique images, motivated history, literature, religion, national culture as a whole. These components become symbolic for the poet and guides his perception of life between light and darkness, peace and war, native and foreign, a feeling of the warm memories of the past and a feeling of despair related to the present and future. The article highlights the decoded symbolic meaning of basic archetypes of cultural context in the author’s works. The comparisons are divided into three groups: 1) comparisons of mother, wife, son, Ukraine, Kyiv with the world of unforgettable memories of a happy life; 2) comparisons of wall, a prisoner’s solitude, the northern landscape (the horizon, dawn, the moon, the sun, peace, prison cell, etc) as a terrible world of hopelessness; 3) comparing the indestructibility of the fighter’s soul to supreme justice. The author of the article discovers hidden textual comparisons both in texts of the poems and in the title of their collection as well as literary allusions, for example, “A Word about Igor’s Regiment” and Shevchenko’s works.
Keywords: anthropological linguistics; linguistics; comparison; individual author's language worldview